Digital-Based BK Services: Counseling Innovation in the Technological Age - Anggia, Anggia (PT. Anagata Sembagi Education, 2025)
Digital-based Guidance and Counseling (BK) services are a form of innovation that emerged in response to the rapid development of information technology. This innovation allows counselors to provide services to students flexibly, efficiently, and in accordance with the needs of the digital generation. This study aims to describe the form of implementation of digital-based BK services, their benefits, and the challenges faced in their implementation. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation in several high schools in Indonesia. The results of the study show that digital BK services are able to increase the accessibility of counseling services, encourage active student participation, and expand the reach of psychopedagogical information. However, there are challenges such as limited technological infrastructure, counselor digital competence, and data privacy issues. Therefore, collaboration between schools, government, and technology providers is important to maximize the potential of this service. Digital-based BK services are believed to be a strategic solution in responding to the dynamics of counseling needs in the digital era, as well as an adaptive step towards an inclusive and responsive education system to developments in the era.